The Effect Of Addition Of Limestone Powder And Gypsum As Isolator Media On Low Carbon Steel SMAW Welding - Muh Anhar; Betti Ses Eka Polonia (Journal of Applied Engineering and Technological Science (JAETS), 2021)
Metal connection due to heat with or without the influence of pressure or metallurgical bonds caused by attractive forces between atoms. DIN (Deutsche Industrie Normen) state that metallurgical bonding of metal or guide metal joints in a melted or liquid state. This study aims to determine the effect of limestone powder and gypsum as an insulating medium in SMAW (Shielded metal arc welding) welding. This study using experimental methods with SMAW welding. Welding metal cooled with limestone media has a harder hardness than gypsum and air media, which is limestone has a thermal conductivity value of 3.897 W / mºC. In comparison, gypsum has a thermal conductivity value of 1.39 W/mºC, and air has a thermal conductivity value of 0.023 J/msºC, so limestone is a better insulator than gypsum and air. The greater the conductivity value of the object, the better the thermal conductivity of the metal and the more complicated the weld metal and the lower the thermal conductivity value, the softer the metal hardness, limestone has a thermal conductivity value of 3.897 W / mºC while gypsum has a thermal conductivity value of 1, 39 W / mºC and air have a thermal conductivity value of 0.023 J / msºC, proving that the lower the conductivity value, the hardness of the weld metal is getting softer, but in the HAZ section it proves that the lower the conductivity value, the more complex the hardness in the HAZ section.